Urban Demand for Wild Foods in Northeast Thailand: A survey of edible wild species sold in the Khon Kaen municipal market - Shirai, Yuko; Rambo, A Terry (Ethnobotany Research and Applications, 2014)
Rural people in Northeast Thailand consume a wide range of wild species. Little is known, however, about the extent to which the urban populations of the region’s rapidly growing towns and cities consume these products, and no detailed study has been made of the edible wild species that are sold in urban markets. To help fill this knowledge gap, this paper presents findings of a survey about the wild species sold in the main urban market in Khon Kaen Municipality. The survey included identification of all species of plants, fungi, and animals being sold and recording of the quantities and prices of each species. Data were obtained by interviewing vendors selling these products in the market on 18 randomly selected nights in the dry season and 12 nights in the rainy season. The diversity of wild species sold in the market is high. Eighty-one species were identified, of which 54 were plants, 6 were fungi, and 21 were animals. Species diversity was greater in the rainy season, when 65 species were on sale, than in the dry season, when 49 species were available. Plant species were much more diverse in the rainy season than in the dry season, reflecting the better growth conditions for vegetation when water is not a limiting factor. Many species were available only in a specific season. The wild species were obtained from several different habitats. Upland fields were the habitat for the largest number of species, followed by house areas, forests, and paddy fields. Gardens and aquatic ecosystems were habitats for a smaller number of species. The supply-shed for the urban market in Khon Kaen Municipality is quite a large one. Wild species sold in the market are obtained from 8 provinces in the Northeast, although rural areas of Khon Kaen Province itself are the source of the largest number of species. Collection of wild species to supply the urban market can have both negative and positive effects on rural biodiversity in Northeast Thailand. In their desire to earn cash income, villagers may over-exploit some of these species, causing wild populations to decline in numbers or even become locally extinct. On the other hand, villagers may intensify their efforts to cultivate them so as to allow more stable production, thus contributing to biodiversity conservation. This has already begun to happen in the case of some highly valued species.